Inactivation of the glutathione peroxidase GPx4 by the ferroptosis‐inducing molecule RSL3 requires the adaptor protein 14‐3‐3ε. Issue 4 (20th October 2019) - Vučković, Ana‐Marija; Bosello Travain, Valentina; Bordin, Luciana; Cozza, Giorgio; Miotto, Giovanni; Rossetto, Monica; Toppo, Stefano; Venerando, Rina; Zaccarin, Mattia; Maiorino, Matilde; Ursini, Fulvio; Roveri, Antonella
Abstract : Ras‐selective lethal small molecule 3 (RSL3), a drug candidate prototype for cancer chemotherapy, triggers ferroptosis by inactivating the glutathione peroxidase glutathione peroxidase 4 (GPx4). Here, we report the purification of the protein indispensable for GPx4 inactivation by RSL3. Mass spectrometric analysis identified 14‐3‐3 isoforms as candidates, and recombinant human 14‐3‐3ε confirms the identification. The function of 14‐3‐3ε is redox‐regulated. Moreover, overexpression or silencing of the gene coding for 14‐3‐3ε consistently controls the inactivation of GPx4 by RSL3. The interaction of GPx4 with a redox‐regulated adaptor protein operating in cell signaling further contributes to frame it within redox‐regulated pathways of cell survival and death and opens new therapeutic perspectives. Abstract :